1972
DOI: 10.1111/j.1365-2672.1972.tb03703.x
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Procedures for Enumerating Bacteria in Activated Sludge

Abstract: A procedure for counting viable heterotrophic bacteria in activated sludge was evolved from a study of the effects of modifications to procedures at the different stages of enumeration. Optimal counts were obtained with Casitone-glycerol-yeast extract agar (CGY) with incubation for 6 days at 22". Homogenization of mixed liquor was conveniently performed, with minimal lethal effect on the bacteria, by treating samples, diluted 1/10 in sodium tripolyphosphate solution (5 mg/l), in a boiling tube immersed in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

1977
1977
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(24 citation statements)
references
References 18 publications
0
24
0
Order By: Relevance
“…Artificial river water (ARW) (41), which was used for enrichment of BPF-degrading bacteria from a river water sample, contained (per liter of ultrapure water) 21 (28) containing BPF at 0.32 mM (1/10CGYF) was used to isolate BPF-degrading bacteria. The isolates were routinely maintained on CGY medium.…”
Section: Methodsmentioning
confidence: 99%
“…Artificial river water (ARW) (41), which was used for enrichment of BPF-degrading bacteria from a river water sample, contained (per liter of ultrapure water) 21 (28) containing BPF at 0.32 mM (1/10CGYF) was used to isolate BPF-degrading bacteria. The isolates were routinely maintained on CGY medium.…”
Section: Methodsmentioning
confidence: 99%
“…CGY agar (Pike et al, 1972) was used except where otherwise stated. It contained (g 1-l): Casitone, 5 ; glycerol, 5 ; yeast extract, I ; and agar (Oxoid no.…”
Section: Methodsmentioning
confidence: 99%
“…Comparative studies have shown that different media offer advantages for the recovery of different organisms. Pike et al (1972) found Casitone glucose yeast extract agar (CGY) gave the highest median counts for the enumeration of bacteria from activated sludge. They also showed that approximately 17 % fewer organisms are recovered on nutrient agar, as used by Allen (1g44), than on CGY.…”
Section: Introductionmentioning
confidence: 99%
“…Formation of aggregates in the incubation media made accurate counts difficult. In media where aggregation had occurred, 1 to 5 m1 of the fixed samples were incubated for approximately 5 min with an equal volume of 5 mg 1-' sodium tripolyphosphate solution (Pike et al, 1972) and sonicated for 30 S in a Dawe Sonicleaner Type 6441 A prior to staining with acridine orange. Microbial biomass was calculated from cell numbers and mean volumes measured by means of the scanning electron microscopy method described by .…”
Section: Microbial Numbers and Biomassmentioning
confidence: 99%